PENGEMBANGAN SISTEM INVENTARISASI BARANG MENGGUNAKAN LOAD CELL DAN CHATBOT TELEGRAM BERBASIS ARDUINO - Kevin Zamzami (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The distribution and trading business has great potential in the Indonesian economy. However, manual inventory monitoring is often inefficient and can lead to stock shortages. Therefore, an ultrasonic and load cell sensor-based tool is needed that aims to automatically control the warehouse by monitoring the inventory of stock items and sending notifications via Telegram ChatBot when the stock runs out. The method involves Arduino Uno, NodeMCU ESP8266, load cell sensor, ultrasonic sensor, and Telegram application. The results show that this tool helps businesses track stock and receive notifications when stock runs out. The conclusion of this research is that inventory detection tools using sensors, microcontrollers, and IoT technology can simplify stock monitoring.